Temporal Microbial Community Dynamics Within a Unique Acid Saline Lake - Ghori, Noor-Ul-Huda; Wise, Michael J.; Whiteley, Andrew S. (Frontiers in Microbiology, 2021)
Lake Magic is an extremely acidic, hypersaline lake found in Western Australia, with the highest concentrations of aluminium and silica in the world. Previous studies of Lake Magic diversity have revealed that the lake hosts acid- and halotolerant bacterial and fungal species. However, they have not canvassed microbial population dynamics across flooding, evapo-concentration and desiccation stages. In this study, we used amplicon sequencing and potential function prediction on sediment and salt mat samples. We observed that the bacterial and fungal diversity in Lake Magic is strongly driven by carbon, temperature, pH and salt concentrations at the different stages of the lake. We also saw that the fungal diversity decreased as the environmental conditions became more extreme. However, prokaryotic diversity was very dynamic and bacteria dominated archaeal species, both in abundance and diversity, perhaps because bacteria better tolerate the extreme variation in conditions. Bacterial species diversity was the highest during early flooding stage and decreased during more stressful conditions. We observed an increase in acid tolerant and halotolerant species in the sediment, involved in functions such as sulphur and iron metabolism, i.e., species involved in buffering the external environment. Thus, due to activity within the microbial community, the environmental conditions in the sediment do not change to the same degree as conditions in the salt mat, resulting in the sediment becoming a safe haven for microbes, which are able to thrive during the extreme conditions of the evapo-concentration and desiccation stages.